Prosocial and proactive "safety citizenship behaviour" (SCB): The mediating role of affective commitment and psychological ownership. (April 2018) - Curcuruto, Matteo; Griffin, Mark A.
Highlights: Affiliative and change-oriented SCBs are two distinct forms of safety citizenship. Organizational support and team safety climate are situational antecedents of SCB. Affective commitment and psychological ownership are person antecedents of SCB. Psychological ownership plays a mediational role on change-oriented SCB . Affective commitment plays a mediational role on affiliative SCB . Abstract: Safety citizenship behaviour (SCB) is an important participation factor in work-groups. Our study aims to study the influence of some antecedents of this safety-specific dimension of organizational citizenship. In the light of the current research stream that distinguishes between prosocial vs. proactive forms of organizational citizenship, we will investigate the effects of the following variables: organizational support for safety participation; team safety climate; psychological ownership toward the management of safety; affective commitment toward the organization. The research was conducted in a multinational chemical industry (N = 314). Prosocial oriented forms of SCB (safety stewardship) were mainly related to the influence of affective dimensions of organizational belongingness (affective commitment) . On the other hand, proactive oriented forms of SCB (safety voice) showed higher linkages with the internalization of safety promotion instances (psychological ownership) . The conclusions of the article include conceptual implications for academic research and managerial practice. The aim of this is to support a broader safety citizenship orientation by the workforce in the management of safety related instances in the workplace.